Current Status of Angiotensin Receptor Blocker Recalls. Issue 6 (December 2019) - Gunasekaran, Pradeep Moon; Chertow, Glenn M.; Bhalla, Vivek; Byrd, James Brian
Abstract : Losartan was the ninth most prescribed drug in the United States in 2016, and several other angiotensin-II receptor blockers (ARBs) are widely prescribed. Since July 2018, >2 dozen specific ARB products have been recalled owing to the presence of potentially carcinogenic nitrosamine impurities in selected lots. As is the case with all U.S. drug recalls, the ARB recalls have been voluntary on the part of the companies involved. In April 2019, the Food and Drug Administration categorized marketed ARB products with respect to nitrosamine impurities: (1) not present, (2) to be determined with no prior lots removed from the market (TBD), or (3) to be determined in the context of prior lots having been removed from the market (TBD*). The data were structured as hundreds of rows of products. Owing to the complexity of these data, more than a year into the recalls, it remains difficult for clinicians to understand which ARB products are free of impurities.